Value Engineering and Critical Path Method in Elevated Railway Working Light Rail Transit (LRT) Projects - Afionita Imam Saputri, Albert Eddy Husin, Chandra Fany Abdillah, Mohamad Imam Suradi Fadilah, Susanto Firdaos, Michael Kelvin Eddy Husin (International Journal of Advanced Science and Technology, 2020)
Increasing the number of vehicles, both public forces and private transportation that use roads and cause various transportation problems, one of which is traffic jams. Light Rail Transit (LRT) is a fast transportation system that connects Jakarta with other cities such as Bogor and Bekasi which are considered more efficient in overcoming congestion because it can be easily integrated with other modes of transportation. To fulfill project performance in terms of cost and time, the value engineering and critical path method methods are used. By using statistical analysis methods using the Statistical Package for Social Sciences (SPSS) regarding the factors that influence the application of value engineering and critical path methods in the construction of Light Rail Transit. The results of this study indicate the influencing factors include: Data Analysis, Information Phase, Initial Planning, Work Method Approach, Low Labor Productivity, Critical Path Determination, FAST Function Stages, Efficiency, Evaluation Stage, Creativity Stage